2006
DOI: 10.1093/jn/136.3.793s
|View full text |Cite
|
Sign up to set email alerts
|

Aged Garlic Extract May Be Safe for Patients on Warfarin Therapy

Abstract: Garlic has been known to have antiplatelet properties. Because of the lack of major clinical data regarding the safety of concomitant use of garlic supplements and anticoagulants, we decided to evaluate the safety of using garlic extract along with oral anticoagulation therapy. During this project we tested aged garlic extract (AGE), a commercial garlic preparation, with warfarin (Coumadin). Sixty-six (66) patients were screened for a double-blind, randomized, placebo-controlled pilot study. Fifty-two (52) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 19 publications
2
78
0
3
Order By: Relevance
“…These reports, however, contained inadequate information to assess the likelihood of an interaction. Recently, Macan and colleague [117] have suggested that AGE is relatively safe and poses no serious hemorrhagic risk for closely monitored patients on warfarin therapy.…”
Section: Herb-drug Interactionsmentioning
confidence: 99%
“…These reports, however, contained inadequate information to assess the likelihood of an interaction. Recently, Macan and colleague [117] have suggested that AGE is relatively safe and poses no serious hemorrhagic risk for closely monitored patients on warfarin therapy.…”
Section: Herb-drug Interactionsmentioning
confidence: 99%
“…However, a recent double-blinded placebo controlled pilot study by Macan et al (2006) of 48 patients tested admnistration of aged garlic extract with concomitant use of warfarin (Coumadin®) and found no evidence of increased hemorrhage in either the placebo or the garlic users. The authors from UCLA determined that "the results suggest that AGE is relatively safe and poses no serious hemorrhagic risk for closely monitored patients on warfarin oral anticoagulation therapy.…”
Section: Side Effects/ Contraindicationsmentioning
confidence: 99%
“…47 However, in healthy volunteers, garlic in combination with warfarin was shown to have no effect on INR or bleeding risk over short-term follow-up. 36,44 Garlic should be used with caution in those on oral anticoagulants, as garlicassociated postoperative bleeding 48 55 which was confirmed in a more recent trial (CAMUS) funded by the NCCIH that used up to 960 mg/day of saw palmetto extracts in men with moderate lower urinary tract symptoms. 56 Reported adverse reactions from saw palmetto include sexual dysfunction, fatigue, tachycardia, angina pectoris, extrasystole, 57 hypertension, 58 intraoperative hemorrhage, 59 bleeding susceptibility, 60 pancreatitis 61 and cholestatic hepatitis.…”
Section: Cranberrymentioning
confidence: 98%
“…43 However, other trials have shown no significant effects on total cholesterol, low-density-lipoprotein cholesterol, blood pressure, platelet count or triglycerides in patients taking garlic supplements. 36,44 Garlic is believed to have antithrombotic activity 45 and decrease platelet aggregation, 46 which can increase clotting time and risk of bleeding when taken with anticoagulants such as warfarin. 47 However, in healthy volunteers, garlic in combination with warfarin was shown to have no effect on INR or bleeding risk over short-term follow-up.…”
Section: Cranberrymentioning
confidence: 99%